Postoperative Tourniquet Pain in Patients Undergoing Foot and Ankle Surgery - Ashish Shah MD; Eva Lehtonen BS; Samuel Huntley BSc; Harshadkumar Patel MD; John Johnson BSc; Zachariah Pinter BS; Sameer Naranje MD, MRCS; Sung Lee BS; Promil Kukreja MD, PhD; Ilya Gutman BS (Foot & Ankle Orthopaedics, 2018)
Category: Other Introduction/Purpose: The tourniquet is commonly used in orthopedic surgeries on the upper and lower extremities to reduce blood loss, improve visualization, and expedite the surgical procedure. However, tourniquets have been associated with multiple local and systemic complications, including postoperative pain. Guidelines vary regarding ideal tourniquet pressure and duration, while the practice of fixed, high tourniquet pressures remains common. The relationship between tourniquet pressure, duration, and postoperative pain has been studied in various orthopaedic procedures, but these relationships remain unknown in foot and ankle surgery. The purpose of this study was to assess for correlation between excessive tourniquet pressure and duration and the increased incidence of tourniquet pain in foot and ankle surgery patients. Methods: Retrospective chart review was performed for 132 adult patients who underwent foot and ankle surgery with concomitant use of intraoperative tourniquet at a single institution between August and December of 2015. Patients with history of daily opioid use of 30 or more morphine oral equivalents for greater than 30 days, patients who underwent foot and ankle surgery without regional nerve block, patients deemed to have failed regional nerve block, and patients who underwent foot and ankle surgery without tourniquet use were excluded. Patient’s baseline systolic blood pressure, tourniquet pressure and duration, tourniquet deflation time, tourniquet reinflation pressure and duration, intraoperative blood pressure and heart rate changes, intra-operative opioid consumption, PACU pain scores, PACU opioid consumption, and PACU length of stay were collected. Statistical correlation between tourniquet pressure and duration and postoperative pain scores, pain location, narcotic use, and length of stay in PACU was assessed using linear regression in SPSS. Results: Average age of patients was 47.6 years (Range: 16 - 79). Tourniquet pressure was 280 mmHg in 90.6% of patients (Range: 250-300 mmHg). Only 3.8% percent of patients had tourniquet pressures 100-150 mmHg above systolic blood pressure. Mean tourniquet time was 106.2 ± 40.1 min. Tourniquet time showed significant positive correlation with morphine equivalents used in the perioperative period (N = 121; r = 0.406; p < 0.001). Long tourniquet times (= 90 minutes) were associated with greater intraoperative opioid use than short tourniquet times (= 90 minutes) (19 mg ± 22 mg vs. 5 mg ± 11.6 mg; p <0.001). Tourniquet duration and PACU length of stay had a positive association (R2 = 0.4). Conclusion: The majority of cases of foot and ankle surgery at our institution did not adhere to current tourniquet use guidelines, which recommend tourniquet pressure between 100 and 150 mmHg above patient’s systolic blood pressure. Prolonged tourniquet times at high pressures not based on limb occlusion pressure, as observed in our study, lead to increased pain and opioid use and prolonged time in PACU. Basing tourniquet pressures on limb occlusion pressures could likely improve the safety margin of tourniquets, however randomized studies need to be completed to confirm this.